Evaluation of ciprofloxacin, prednisolone, and infliximab effects on liver functions in acetic acid-induced ulcerative colitis rat model - Oyesola, Olusoji; Adeojo, Adebowale; Olayemi, Oluwaseye; Ojo-Adebayo, Eunice; George, Emmanuel (Journal of Associated Medical Sciences, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by recurring episodes of gastrointestinal inflammation and damage, affecting millions worldwide. Emerging evidence suggests a complex relationship between UC and liver dysfunction, with increased risk of hepatotoxicity and liver-related disorders. Objectives: To investigate the effects of ciprofloxacin, prednisolone, and infliximab on liver function in an acetic acid-induced UC rat model. Materials and methods: Fifty male Sprague-Dawley rats were divided into five groups of ten rats each: control, UC, ciprofloxacin, prednisolone, and infliximab group. UC was induced with 2 ml of 4% acetic acid solution transrectal. Liver function tests (AST, ALT, ALP), oxidative stress markers (MDA), protein synthesis (total protein, albumin), and bilirubin processing were evaluated, and histological examination of liver tissues was performed. Results: The UC group showed significant increase in liver function enzymes (ALP, AST, ALT), oxidative stress markers (MDA) and significant decrease in total protein, albumin, total bilirubin and conjugated bilirubin level when compared with the control group. Respective treatment groups demonstrated improved liver enzyme levels, reduced oxidative stress, enhanced protein synthesis and bilirubin processing. Histological examination revealed improved liver architecture and reduced inflammation in treatment groups when compared with the UC group. Conclusion: This study provides evidence that ciprofloxacin, prednisolone, and infliximab exert protective effects on liver function in acetic acid induced UC model. These findings suggest potential benefits of these therapies in mitigating liver damage associated with UC, highlighting the importance of considering liver health in UC management.